Academic, behavioural and quality of life outcomes of slight to mild hearing loss in late childhood: a population-based study. Issue 11 (11th May 2019) - Wang, Jing; Quach, Jon; Sung, Valerie; Carew, Peter; Edwards, Ben; Grobler, Anneke; Gold, Lisa; Wake, Melissa
Abstract : Objective: To investigate the associations of hearing thresholds and slight to mild hearing loss with academic, behavioural and quality of life outcomes in children at a population level. Methods: Design and participants: children aged 11–12 years in the population-based cross-sectional Child Health CheckPoint study within the Longitudinal Study of Australian Children. Audiometry: mean hearing threshold across 1, 2 and 4 kHz (better and worse ear); slight/mild hearing loss (threshold of 16–40 decibels hearing loss (dB HL)). Outcomes: National Assessment Program – Literacy and Numeracy, language, teacher-reported learning, parent and teacher reported behaviour and self-reported quality of life. Analysis: linear regression quantified associations of hearing threshold/loss with outcomes. Results: Of 1483 children (mean age 11.5 years), 9.2% and 13.1% had slight/mild bilateral and unilateral hearing loss, respectively. Per SD increment in better ear threshold (5.7 dB HL), scores were worse on several academic outcomes (eg, reading 0.11 SD, 95% CI 0.05 to 0.16), parent-reported behaviour (0.06 SD, 95% CI 0.01 to 0.11) and physical (0.09 SD, 95% CI 0.04 to 0.14) and psychosocial (0.06 SD, 95% CI 0.01 to 0.11) Pediatric Quality of Life Inventory (PedsQL). Compared with normally hearing children, children with bilateral slight/mild losses scored 0.2–0.3 SDs lower in sentence repetition, teacher-reported learning and physical PedsQL but not other outcomes. Similar but attenuated patterns were seen in unilateral slight/mild losses. Conclusions: Hearing thresholds and slight/mild hearing loss showed small but important associations with some child outcomes at 11–12 years. Justifying hearing screening or intervention at this age would require better understanding of its longitudinal and indirect effects, alongside effective management and appropriate early identification programmes.